Environmental and exergy benefit of nanofluid-based hybrid PV/T systems. (1st September 2016) - Hassani, Samir; Saidur, R.; Mekhilef, Saad; Taylor, Robert A.
Highlights: Environmental and ExPBT analysis of different PV/T configurations is presented. The exergy payback time of nanofluid-based hybrid PV/T system is about 2 years. Nanofluid-based hybrid PV/T system is a reliable solution for pollution prevention. Nanofluid-based hybrid PV/T system is highly recommended at high solar concentration. Abstract: Photovoltaic/thermal (PV/T) solar systems, which produce both electrical and thermal energy simultaneously, represent a method to achieve very high conversion rates of sunlight into useful energy. In recent years, nanofluids have been proposed as efficient coolants and optical filter for PV/T systems. Aim of this paper is to theoretically analyze the life cycle exergy of three different configurations of nanofluids-based PV/T hybrid systems, and compare their performance to a standard PV and PV/T system. Electrical and thermal performance of the analyzed solar collectors was investigated numerically. The life cycle exergy analysis revealed that the nanofluids-based PV/T system showed the best performance compared to a standard PV and PV/T systems. At the optimum value of solar concentration C, nanofluid-based PV/T configuration with optimized optical and thermal properties produces ∼1.3 MW h/m 2 of high-grade exergy annually with the lowest exergy payback time of 2 years, whereas these are ∼0.36, ∼0.79 MW h/m 2 and 3.48, 2.55 years for standard PV and PV/T systems, respectively. In addition, the nanofluids-based PV/T system can prevent the emissions of about 448 kg CO2 eq m −2 yr −1 . Overall, it was found that the nanofluids-based PV/T with optimized optical and thermal properties has potential for further development in a high-concentration solar system.